A Review on Optical Fibre Sensor Topology and Modulation Technique - S., Nurulain; Nor Mazlee, Norazmi; M. R., Salim; Hadi, Manap (Penerbit Universiti Malaysia Pahang, 2017)
This paper reviews of optical fibre sensor and it focuses on sensor topology and modulation techniques. Fundamentals and working principles of optical fibre based sensing system are thoroughly explained. Particular interest is given on various technique and highlight its advantages and disadvantages. The objective of the review is to evaluate their respective suitability for use as a sensor in different environment or it can provide an alternative method of optical sensing in any particular sector